Student activities: Cyber Security SIG - the journey of empowering Cyber Security professionals - Mansor, Hafizah (2024)
Cyber Security Special Interest Group(SIG), IIUM is established with the objectives of educating students and the IIUM community with cybersecurity knowledge and awareness. Our activities range from awareness programmes, and technical workshops to cater for the different needs and interests of students.